Identity of the coral-associated pontoniine shrimp species, Coralliocaris nudirostris (Heller, 1861) and C. venusta Kemp, 1922 (Crustacea: Decapoda: Palaemonidae), with descriptions of two new species - Mitsuhashi, Masako; Takeda, Masatsune (Zootaxa, 2008)
Two species of the pontoniine shrimp genus Coralliocaris, C. venusta Kemp, 1922 and C. nudirostris (Heller, 1861), are reviewed based on the type specimens and additional material from the Indo-West Pacific. Two colour morphs previously recognized in C. venusta can be separated into two species on the basis of presence or absence of a concavity on the medial surface of the first pereiopod fingers. The presence of a concavity on the first pereiopod fingers indicates that the ‘white patched morph’ of C. venusta is referable to C. venusta sensu stricto, and that this species is conspecific with C. nudirostris, whereas the colour morph (‘black striated morph’) characterised by the absence of the concavity, belongs to a new species, C. sandyi sp. nov. A further new species named C. labyrintha sp. nov. can be separated from the former by the colour pattern in life, a moderately angled supraorbital eave, usually more numerous rostral teeth, and proportionally slenderer fingers of the first pereiopod. Colour photographs and drawings of fresh specimens of C. nudirostris and the two new species are provided, and an updated key to the genus is given to facilitate identification.